Scientific Attitude and Its Effect on Students’ Productivity - Fatonah, S.; Prasetyo, Z. K.; Utami, A. D.; Chasanah, U.; Lusiana, L.; Siregar, V. V. (Jurnal Pendidikan IPA Indonesia, 2023)
There are seven indicators of scientific attitudes: curiosity, respect for data/facts, critical thinking, discovery and creativity, open-mindedness and cooperation, perseverance, and sensitivity to the environment. Scientific attitudes correlate with productivity. However, the relation between productivity and each scientific attitude indicator are unexplored. This study aims to determine the effect of indicator of scientific attitudes on undergraduate and postgraduate students’ productivity. The research method used is quantitative with a correlation approach. Data was collected using questionnaires that distributed via Google Forms. The research respondents were randomly selected by distributing Google Forms in the WhatsApp group. The respondents of this study totaled 101 respondents consisting of 44 undergraduate students, 50 postgraduate students and 7 doctoral students. From the research results, the indicators of scientific attitude that correlate with undergraduate students’ productivity are respect for data/facts, critical thinking, as well as discovery and creativity. Meanwhile, indicators of scientific attitude that correlate with postgraduate students’ productivity are curiosity, respect for data/facts, critical thinking, discovery and creativity, as well as perseverance. The overall scientific attitudes got a significance level of 0.050, indicating a significant correlation between the scientific attitude indicator and the productivity of undergraduate students. The significance level of the scientific attitude toward the productivity of postgraduate students was 0.003, so there is a significant correlation between scientific attitudes toward the productivity of postgraduate students. This study concludes that the effect of a scientific attitude on the productivity of postgraduate students is greater than that of undergraduate students. Hence, scientific attitudes influence students’ productivity.